MEASURES OF STRENGTHENING THE ORGANIZATION AND MATERIAL TECHNICAL BASE OF THE TERMIZ STATE PEDAGOGICAL INSTITUTE - Khudoykul MULKAMONOV (Scholar Express Journal, 2024)
This article describes the process of establishing a pedagogical institute in Surkhandarya in the 50s of the 20th century and measures to strengthen the material and technical base of the university. information about going is given.
Keywords: Margilan; department; teacher; institute